(3GdJGQjN GdZjGKjs - (3YHO Gddg Hf aJM Gddg GdZjGK GdHZOGOjs
(3ChdgG (B:s
(3hHYO Ef ef cKQI GdaJf , ef OhQ GdTjN MSf Edi jhefG gPG aNWQ di Cf CcJH gPg GdChQGb HHYV eG LQi ai ReGffG s
(3BNQgG (B:s
(3hHJGQjN jhe GdEKfjf (B15 (3PhGdMLI (B[(3cPG(B] (3SfI (B883 (3YRd cdGHi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B100s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B80 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs